2008
DOI: 10.3926/jiem.2008.v1in2.p54-76
|View full text |Cite
|
Sign up to set email alerts
|

AHP approach for supplier evaluation and selection in a steel manufacturing company

Abstract: Supplier selection is one of the most critical activities of purchasing management in supply chain. Supplier selection is a complex problem involving qualitative and quantitative multi-criteria. A trade-off between these tangible and intangible factors is essential in selecting the best supplier. The work incorporates AHP in choosing the best suppliers. The results suggest that AHP process makes it possible to introduce the optimum order quantities among the selected suppliers so that the Total Value of Purcha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…This proves earlier studies that state that quality is an important criterion for vendor evaluation (Tam & Tummala, 2001). Tahriri, Osman et. al (2008) support the results of this study since they also suggested that quality is an important criterion followed by delivery, cost and responsiveness of the vendors.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This proves earlier studies that state that quality is an important criterion for vendor evaluation (Tam & Tummala, 2001). Tahriri, Osman et. al (2008) support the results of this study since they also suggested that quality is an important criterion followed by delivery, cost and responsiveness of the vendors.…”
Section: Resultssupporting
confidence: 86%
“…This is because substitution of the partners has become a common practice in the industry in order for companies to improve their performance and meet the multiple market conditions (Mowshowitz, 1997). The vendor's involvement in research and development activities helps the company with continuous improvement (Tahriri, et al, 2008). A longterm relationship with the vendor is crucial for a firm to be able to effectively fulfill the demands of the customers (Kannan & Tan, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The AHP model is a commonly quantitative approach used for supplier selection in many industries [3][4][5][6][7][8][9][10][11][12][13]. ANP models are also applied to solve the same type of problem on SCM as AHP model [14][15][16], which is a network analysis method that considers hierarchy and interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The biggest challenge with the process for many organizations is that, it involves many conflicting criterion which cost of both qualitative and quantitative metrics. Tahriri, F., et al, 4 explained that being a multi criteria decision problem, trade-offs among multiple criteria is a common practice. This is because each supplier will portray different traits based on the criteria's used.…”
Section: Introductionmentioning
confidence: 99%